Econometric Analysis of the Hot Research of Marxist Theoretical Journals Based on Knowledge Map - Lan Wang; Kai Wang (Discrete Dynamics in Nature and Society)
In recent years, the research on Marxist theory has received a lot of attention. Many studies use quantitative research methods such as statistical keywords and constructing knowledge map to carry out Marxist theoretical analysis. In this paper, by constructing a self-expanding Chinese word separation and self-expanding address data knowledge graph, matching Marxist Chinese addresses based on the full-text indexing knowledge graph, incorporating a weighted pinyin full-text search mechanism to improve the matching accuracy of misspelled addresses, constructing a multiple matching mechanism for Marxist addresses by combining an online geographic parsing interface, and performing semisupervised matching for a small number of difficult addresses, a complete system of Marxist address matching methods is formed. By studying and analyzing the basic orientation and attention to academic hotspots, we can gain insight into the characteristics, rules, and problems of academic hotspots in Marxist theory journals.